Sardonic Attitude of the Roux in the Great Railway Bazar - Upadhyay, Toya Nath (Tribhuvan University Journal, 2018)
This study examines Paul Theroux’s The Great Railway Bazaar (1977) so as to trace his perception on the Asian states, peoples and cultures during his railway journey across Asia in 1973. The study primarily seeks an answer to the question: does Theroux adopt cosmopolitan vision of the contemporary globalized era or follow the colonial vision of the colonial era? The study borrows theoretical concepts of colonial and cosmopolitan visions from Debbie Lisle. In the process of textual analysis, the study also brings theoretical concepts in travel writing theory and criticisms of various critics on the primary text. The study, finally, comes up with a conclusion that Theroux has implicated the colonial vision as it locates numerous evidences of his condescending and sardonic attitude on the Asian states, peoples and cultures.